2019
DOI: 10.1016/j.actpsy.2019.04.005
|View full text |Cite
|
Sign up to set email alerts
|

The time course of colour congruency effects in picture naming

Abstract: In our interactions with people and objects in the world around us, as well as in communicating our thoughts, we rely on the use of conceptual knowledge stored in long-term memory. From a frame-theoretic point of view, a concept is represented by a central node and recursive attribute-value structures further specifying the concept. The present study explores whether and how the activation of an attribute within a frame might influence access to the concept's name in language production, focussing on the colou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Theories of object recognition have suggested that when participants encode and recognize objects, shape is the chief feature (e.g., Biederman, 1987;Tarr & Bu¨lthoff, 1998). However, some studies have also reported that color has a crucial role in object recognition (Nako et al, 2016;Reppa et al, 2020;Teichmann et al, 2019), and, color typicality (i.e., colors typically associated with familiar objects) has been shown to play an essential role in early perceptual processes during object recognition (e.g., Lu et al, 2010;Rappaport et al, 2013;Redmann et al, 2019;Tanaka & Presnell, 1999). If bizarreness enhances memory due its cognitive demands, it would seem that color bizarreness should enhance memory.…”
Section: Color Bizarreness Effectmentioning
confidence: 99%
“…Theories of object recognition have suggested that when participants encode and recognize objects, shape is the chief feature (e.g., Biederman, 1987;Tarr & Bu¨lthoff, 1998). However, some studies have also reported that color has a crucial role in object recognition (Nako et al, 2016;Reppa et al, 2020;Teichmann et al, 2019), and, color typicality (i.e., colors typically associated with familiar objects) has been shown to play an essential role in early perceptual processes during object recognition (e.g., Lu et al, 2010;Rappaport et al, 2013;Redmann et al, 2019;Tanaka & Presnell, 1999). If bizarreness enhances memory due its cognitive demands, it would seem that color bizarreness should enhance memory.…”
Section: Color Bizarreness Effectmentioning
confidence: 99%
“…If a picture of a banana is presented in yellow, it is recognized faster than if it is presented in an achromatic way or in an atypical color such as purple, indicating a better access to the object concept when the typical object color is present. In picture naming tasks, HCD objects are named faster when presented in their typical colors compared with when they are presented in grayscale format (e.g., Redmann, FitzPatrick, & Indefrey, 2019;Redmann, FitzPatrick, Hellwig, & Indefrey, 2014; see also the meta-analysis by Bramão, Reis, Petersson, & Faísca, 2011). Atypical color presentation simultaneously or just before picture presentation interferes with picture naming of a HCD object (Redmann et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In picture naming tasks, HCD objects are named faster when presented in their typical colors compared with when they are presented in grayscale format (e.g., Redmann, FitzPatrick, & Indefrey, 2019;Redmann, FitzPatrick, Hellwig, & Indefrey, 2014; see also the meta-analysis by Bramão, Reis, Petersson, & Faísca, 2011). Atypical color presentation simultaneously or just before picture presentation interferes with picture naming of a HCD object (Redmann et al, 2019). It is not clear, however, whether such effects on naming latencies arise at the stage of object recognition or reflect an influence of color information on lexical retrieval.…”
Section: Introductionmentioning
confidence: 99%